MENGUKUR DIMENSI KOGNISI: PENDEKATAN ALGORITMA DALAM ANALISIS BAHASA - Agussalim, Andi; Baso, Yusring S.; Zuhriah, Zuhriah (Jurnal Sarjana Ilmu Budaya, 2024)
This research explores the relationship between cognitive dimensions and the implementation of linguistic algorithms in language analysis. The main findings show that linguistic algorithms are capable of replicating a number of cognitive patterns, including information extraction, context understanding, syntactic analysis, maintenance of discourse cohesion, and adaptability. By pursuing these cognitive patterns, linguistic algorithms can increase their response capabilities and complexity in language processing. This research provides a strong theoretical basis for the development of more effective and adaptive language processing systems, paving the way for approaches that are more responsive to linguistic dynamics and contextual changes.